Effect of Interfacial Engineering in Solid‐State Nanostructured Sb2S3 Heterojunction Solar Cells (Adv. Energy Mater. 1/2013). Issue 1 (8th January 2013) - Fukumoto, Takafumi; Moehl, Thomas; Niwa, Yusuke; Nazeeruddin, Md. K.; Grätzel, Michael; Etgar, Lioz
<x xml:space="preserve">Abstract</x> Surface treatment by decyl‐phosphonic acid (DPA) in an inorganic–organic Sb2S3 heterojunction solar cell reduces the recombination and increases the open circuit voltage and the fill factor. The DPA attaches to both surfaces, the uncovered TiO2 surface and the Sb2S3 surface. This cell produces a power conversion efficiency of 3.9% under 1 sun intensity. More details can be found in the article by Takafumi Fukumoto, Lioz Etgar, and co‐workers on page 29. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>